PENGARUH RASIO-RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA (Studi Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2017-2019) - Heru Cahyo; Siti Muntahanah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze the effect of capital ratio, efficiency ratio, liquidity ratio and profitability ratio on profit growth in banking companies listed on the Indonesia Stock Exchange (IDX) in 2017 - 2019. This type of research is quantitative. The sampling technique used a purposive sampling approach. The results show that capital ratio and profitability ratio had a significant positive effect on profit growth on profit growth in banking companies listed on the Indonesia Stock Exchange from 2017 to 2019. The efficiency ratio has a significant negative effect on profit growth in banking companies listed on the Indonesia Stock Exchange from 2017 to 2019. Meanwhile, the liquidity ratio has not significant effect on profit growth in banking companies listed on the Indonesia Stock Exchange from 2017 to 2019. The research implication is that the company needs to prioritize financial policies related to capital ratio, efficiency ratio and profitability ratio.